Relationships linking primary production, sea ice melting, and biogenic aerosol in the Arctic. (July 2016) - Becagli, S.; Lazzara, L.; Marchese, C.; Dayan, U.; Ascanius, S.E.; Cacciani, M.; Caiazzo, L.; Di Biagio, C.; Di Iorio, T.; di Sarra, A.; Eriksen, P.; Fani, F.; et al.
Abstract: This study examines the relationships linking methanesulfonic acid (MSA, arising from the atmospheric oxidation of the biogenic dimethylsulfide, DMS) in atmospheric aerosol, satellite-derived chlorophyll a (Chl- a ), and oceanic primary production (PP), also as a function of sea ice melting (SIM) and extension of the ice free area in the marginal ice zone (IF-MIZ) in the Arctic. MSA was determined in PM10 samples collected over the period 2010–2012 at two Arctic sites, Ny Ålesund (78.9°N, 11.9°E), Svalbard islands, and Thule Air Base (76.5°N, 68.8°W), Greenland. PP is calculated by means of a bio-optical, physiologically based, semi-analytical model in the potential source areas located in the surrounding oceanic regions (Barents and Greenland Seas for Ny Ålesund, and Baffin Bay for Thule). Chl- a peaks in May in the Barents sea and in the Baffin Bay, and has maxima in June in the Greenland sea; PP follows the same seasonal pattern of Chl- a, although the differences in absolute values of PP in the three seas during the blooms are less marked than for Chl- a . MSA shows a better correlation with PP than with Chl- a, besides, the source intensity (expressed by PP) is able to explain more than 30% of the MSA variability at the two sites; the other factors explaining the MSA variability are taxonomic differences in the phytoplanktonic assemblages, and transport processes from the DMS source areas to the sampling sites. The taxonomic differences are also evident from the slopes of the correlation plots between MSA and PP: similar slopes (in the range 34.2–36.2 ng m −3 of MSA/(gC m −2 d −1 )) are found for the correlation between MSA at Ny Ålesund and PP in Barents Sea, and between MSA at Thule and PP in the Baffin Bay; conversely, the slope of the correlation between MSA at Ny Ålesund and PP in the Greenland Sea in summer is smaller (16.7 ng m −3 of MSA/(gC m −2 d −1 )). This is due to the fact that DMS emission from the Barents Sea and Baffin Bay is mainly related to the MIZ diatoms, which are prolific DMS producers, whereas in the Greenland Sea the DMS peak is related to an offshore pelagic bloom where low-DMS producer species are present. The sea ice dynamic plays a key role in determining MSA concentration in the Arctic, and a good correlation between MSA and SIM (slope = 39 ng m −3 of MSA/10 6 km 2 SIM) and between MSA and IF-MIZ (slope = 56 ng m −3 of MSA/10 6 km 2 IF-MIZ) is found for the cases attributable to bloomings of diatoms in the MIZ. Such relationships are calculated by combining the data sets from the two sites and suggest that PP is related to sea ice melting and to the extension of marginal sea ice areas, and that these factors are the main drivers for MSA concentrations at the considered Arctic sites. Graphical abstract: Highlights: MSA is measured at Ny Ålesund (78.9°N, 11.9°E) and Thule Air Base (76.5°N, 68.8°W). Primary production (PP) is calculated by a bio-optical model in the surrounding seas. PP explains about the 30% of MSA variability in both the Arctic sites. MSA and sea ice melting are correlated (slope: 39 ng m −3 of MSA/10 6 km 2 ). MSA and ice free marginal ice zone are correlated (slope: 56 ng m −3 of MSA/10 6 km 2 ).